Static Pipeline Network Performance Optimisation Using Dual Interleave Routing Algorithm - Subramaniam, Siva Kumar; Khan, Shariq Mahmood; Titik, Anhar; Nilavalan, Rajagopal (International Islamic University Malaysia (IIUM), 2018)
In the recent years, there is an increasing demand on multi-hop wireless sensor networks (WSN) especially for remote condition and integrity monitoring of oil and gas pipelines. The sensing points are connected through WSN points, known as a wireless communication medium, between the remotely measured locations on a pipeline and a centralised monitoring station, located some distance away. Generally, WSN deployment on a multi-hop linear topology has critical factors that contribute towards overall degrading of network performance proportional to the number of nodes. This is especially true in highly dense networks. In general, such a drawback contributes towards poor network reliability, low network capacity, high latency, and inequality with snowballing effect, increasing in the direction of the destination node. This paper introduces the Dual Interleaving Linear Static Routing (DI-LSR) for a multi-hop linear network with high reliability and efficiency to significantly enhance the overall network performance of a pipeline network. The DI-LSR was tested and analysed according to IEEE 802.11 standard in a various simulation environment for future real-time deployment in a pipeline network.